Iconographic Aspects of the Molotov–Ribbentrop Pact: A Comparative Analysis of Documentary Photographs - Vyšniauskas, Arūnas (Genocidas ir rezistencija, 2024)
Based on the surviving 1939 photographs and their comparative analysis, the article reveals the main visual differences that emerged when photographing two different German-USSR bilateral treaty signing ceremonies. This is important and relevant because in scientific literature, history textbooks and other educational materials, as well as in exhibitions and media articles devoted to history, photographsfrom the signing of the German–Soviet Boundary and Friendship Treaty on 28 September 1939 are often mistakenly used to illustrate the signing of the non-aggression pact concluded between Germany and the USSR in Moscow on 23 August 1939, five weeks earlier. Since these two treaties were signed by the same two people – Vyacheslav Molotov and Joachim von Ribbentrop – at the same desk in the same office of the Chairman of the Council of People’s Commissars of the USSR in the Moscow Kremlin, it is not that easy to distinguish at first glance which treaty is being signed in one photograph or another. The photographs are often confused, arbitrarily choosing the ones that look more expressive for the sake of illustration. The article presents visual material, its analysis, insights and generalisations that will help to avoid the photograph attribution errors that are so common in using old photographs to illustrate the signing of the 23 August 1939 Treaty of Non-Aggression between Germany and the Union of Soviet Socialist Republics.